If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5z + -3 = 2(z + -6) Reorder the terms: -3 + 5z = 2(z + -6) Reorder the terms: -3 + 5z = 2(-6 + z) -3 + 5z = (-6 * 2 + z * 2) -3 + 5z = (-12 + 2z) Solving -3 + 5z = -12 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -3 + 5z + -2z = -12 + 2z + -2z Combine like terms: 5z + -2z = 3z -3 + 3z = -12 + 2z + -2z Combine like terms: 2z + -2z = 0 -3 + 3z = -12 + 0 -3 + 3z = -12 Add '3' to each side of the equation. -3 + 3 + 3z = -12 + 3 Combine like terms: -3 + 3 = 0 0 + 3z = -12 + 3 3z = -12 + 3 Combine like terms: -12 + 3 = -9 3z = -9 Divide each side by '3'. z = -3 Simplifying z = -3
| 2x^2+x=153 | | 12s-18s-19s-13s+-6=18 | | 5+8lnx=9 | | 3(x-8)=4x-6 | | 5h+2h-h-2h-3h=14 | | 3y+y+2y+3y+2=20 | | (-2)(-8)(-1)(-4)= | | -4/7+y=-2/3 | | 5+6x=3x-16 | | 5=0.167+-0.67 | | 8/6=6 | | .3x^2=.6x+.3 | | -2/5=-2/3+s | | x-x/3=2 | | 3-9/6 | | (-5)(1)(-2)(4)(-6)= | | 3/9=x/8 | | 2x^2=13x+15 | | x+x/2=3 | | 6b+-18b+-18b-5b+17b+-15=-7 | | 30x-4000=1000 | | D/6=42 | | 7n+2n-9n+2n-2=14 | | (-2)(-5)(-9)= | | y^2-16y=36 | | 50m-38m-8m-17m+-16=47 | | 33+15w=3-w+4w | | x+x2=3 | | -3x^7y^8(3xz^6+2y^2-4z^2)= | | -7w+3(w+4)=24 | | 4-(m/5)=18 | | 27x^3+9x^2-48x+20=0 |